Manifestation of Generalized Anxiety Disorder and Its Association With Somatic Symptoms Among Occupational and Physical Therapists During the COVID-19 Pandemic - Alnaser, Musaed Z.; Alotaibi, Naser; Nadar, Mohammed Sh.; Manee, Fahad; Alrowayeh, Hesham N. (Frontiers in Public Health, 2022)
Purpose The purpose of the study was to examine the level of generalized anxiety disorder among occupational and physical therapists during treatment sessions and its association with somatic symptoms during the COVID-19 pandemic. Methods A descriptive cross-sectional design was used in this study. Data were collected during the month of April 2021, and the study included occupational and physical therapists who practiced during COVID-19 from March 2020 to March 2021. The generalized anxiety disorder scale (GAD-7) and a modified patient health questionnaire (mPHQ-15) were used to examine self-reported anxiety and somatic symptoms among the study participants. The independent t-test was used to determine differences between groups based on GAD-7 and mPHQ-15 results. Spearman's correlation test and chi-squared test were used to find the relationships between different variables such as anxiety and somatic symptoms. Results The study (n = 98 participants) included 56 occupational and 42 physical therapists. An 84% response rate was achieved. GAD-7 final score was μ = 9.21 ± 5.63 with 27% reporting no anxiety, 14% mild, 38% moderate, and 21% severe. Independent t-tests on GAD-7 scores showed significant differences between therapist specializations [t(96) = −2.256; p = 0.026] and between therapists residing with or without their parents [t(96) = −2.536; p = 0.013]. The mPHQ-15 final score was μ = 9.52 ± 5.54 with 13% reporting no symptoms (n = 13), 20% mild (n = 20), 38% moderate (n = 37), and 29% severe (n = 28). GAD-7 and mPHQ-15 scores were moderately positively correlated [r(96) = 0.569; p <0.000]. The chi-squared test showed a significant association between GAD-7 levels of anxiety and mPHQ-15 levels of somatic symptoms [x2(9, N = 98) = 70.62 p <0.000]. Therapists reported that the quality (76%) and effectiveness (20%) of their rehabilitation services were negatively impacted by the COVID-19 pandemic. Conclusion The majority of study participants experienced moderate to severe anxiety and associated somatic symptoms. During COVID-19, ongoing psychological counseling of healthcare professionals such as occupational and physical therapists is required to maintain positive mental health. Implications for practice are presented.